PCB: going the extra mile while ill? Construction and Validation of a Scale of Presenteeism Citizenship Behavior - Lourenço; Ferreira, A.I. (14th ECPA 14, 2017)
From our knowledge, no published study to date has empirically examined presenteeism as an Organizational Citizenship Behaviour (OCB) dimension. Therefore, a gap on the OCB literature is found, and a core question arises: can OCB “go the extra mile” with the introduction of presenteeism? The current study aims to develop a new construct to measure Presenteeism as a citizenship construct. In addition to the study of the psychometric evidences, this research examines the relationship between helping behaviour, Presenteeism Citizenship Behaviour (PCB) and social capital, arguing that helping behaviour and social capital are both positively related to PCB, with PCB mediating the relationship between the studied constructs. Results from a pool of 383 employees from companies and startups of various different areas of expertise (HLM statistical procedures) revealed that this new instrument possesses good psychometric evidences and that helping behaviour and social capital are both positively related to PCB, with PCB mediating the indirect relationship between the studied relationships. Moreover, organizational commitment impacted the effects of PCB, moderating both the direct relationship of PCB on social capital as well as the indirect influence of helping behaviour (through PCB) on social capital. Insights on the implications of these findings and directions for future research are also discussed.